Гидравлическое сопротивление системы многорядных углублений цилиндрической формы на плоской поверхности - Халатов, А. А.; Онищенко, В. Н. (Eastern-European Journal of Enterprise Technologies, 2009)
The results of experimental research of hydraulic resistance of the multi-row system of the dimples cylindrical form are presented with a sharp edge on a flat surface. It is shown that the use two and five rows systems results in the losses of pressure, insignificantly exceed losses on a flat surface. Multiplying the amount of rows of dimples is results in substantial growth of hydraulic resistance